CITY AND ‘COLONIAL GOVERNANCE’ IN LATE COLONIAL INDONESIA: TOWARDS AN AGENDA FOR HISTORICAL RESEARCH - Wahid, Abdul (Paramita: Historical Studies Journal, 2018)
Urban history is a rich and challenging field of study, which is relatively new in Indonesia. In last decade, a body of literature have been produced which examine various aspects of Indonesian urban history of the colonial period. Yet, there are still many other aspects of Indonesian urban history that is still relatively unexplored and needs further research. One of them is that the concerns with the city management, institutional arrangement, and administrative system in general. These aspects are very important to be known not only to understand how cities were governed at the time, but also to see the continuity of their legacies in the subsequent period. Indonesian cities today inherit many kinds of institutional legacies, particularly from the colonial period. Through an extensive literature overview, this paper seeks to discuss several main aspects of city management system of urban Indonesia in late colonial period, based on which it proposes some important research agenda that needs to be carried out to complement our historical comprehension on Indonesian urban history.Ã‚Â Sejarah perkotaan merupakan sebuah tema kajian yang relatif baru berkembang di Indonesia yang cukup kaya dan menantang. Dalam dekade terakhir, sejumlah besar studi telah dihasilkan mengkaji sejumlah aspek sejarah perkotaan di Indonesia masa kolonial. Namun demikian, masih banyak aspek lainnya dari sejarah perkotaan Indonesia yang belum di-sentuh dan membutuhkan kajian lebih lanjut. Di antaranya adalah berkenaan dengan tata kelola perkotaan, tata kelembagaan, dan sistem administrasi perkotaan secara keseluruhan. Aspek-aspek tersebut sangat penting dikaji selain untuk mengetahui sejarah penge-lolaan kota pada waktu itu, juga untuk melihat kesinambungan warisannya pada periode berikutnya. Kota-kota di Indonesia dewasa ini memiliki banyak sekali warisan kelembagaan, terutama dari periode kolonial. Melalui studi literatur yang ekstensif, paper ini membahas berbagai aspek penting dari sistem pengelolaan perkotaan Indonesia pada masa kolonial, dan kemudian mengusulkan berbagai agenda penelitian penting yang bisa dilakukan untuk melengkapi pemahaman historis tentang sejarah perkotaan Indonesia.Ã‚Â